Psychiatric diagnostic interviews for children and adolescents: A comparative study - Angold, Adrian (2012)
OBJECTIVE: To compare examples of 3 styles of psychiatric interviews for youth: the Diagnostic Interview Schedule for Children (DISC) (“respondent-based”), the Child and Adolescent Psychiatric Assessment (CAPA) (“Interviewer-based”), and the Development and Well-Being Assessment (DAWBA) (“expert judgment”). METHOD: Roughly equal numbers of males and females and White and African American participants aged 9–12 and 13–16 were recruited from primary care pediatric clinics. Participants (N=646) were randomly assigned to receive two of the three interviews, in counterbalanced order. Five modules were used: any depressive disorder, anxiety disorders, oppositional defiant disorder, conduct disorder, attention deficit-hyperactivity disorder. At 2 sessions about 1 week apart, parent and child completed 1 of 2 interviews plus 5 screening questionnaires. RESULTS: When interviewed with the DAWBA, 17.7% of youth had 1 or more diagnoses, compared with 47.1% (DISC) and 32.4% (CAPA). The excess of DISC diagnoses was accounted for by specific phobias. Agreement between interview pairs was .13–.48 for DAWBA-DISC comparisons, .21–.61 for DISC-CAPA comparisons, and .23–.48 for CAPA-DAWBA comparisons. DAWBA cases were associated with higher parent-report questionnaire scores than DISC/DAWBA cases, but equivalent child-report scores. CONCLUSIONS: The DAWBA is shorter and cases were probably more severe, making it a good choice for clinical trials, but the user cannot examine the data in detail. The DISC and CAPA are similar in length and training needs. Either would be a better choice where false negatives must be avoided, as in case-control genetic studies, or when researchers need to study individual symptoms in detail.